2000
DOI: 10.1080/000164700317381199
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of local recurrence of soft tissue sarcoma: 205 patients from the Scandinavian Sarcoma Group Register

Abstract: From the Scandinavian Sarcoma Group Register, information on 1,224 surgically-treated patients with soft tissue sarcoma (STS) of the extremity or trunk wall, diagnosed between 1987 and 1995, was collected. 205 patients, one third of whom were referred to a center with a local recurrence, had a total of 284 local recurrences. This analysis describes the treatment for these local recurrences, complications and risk of further recurrences. 169 patients were surgically treated for their first local recurrence. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 29 publications
4
30
1
2
Order By: Relevance
“…The studies cannot be readily compared with ours since patients with recurrent sarcoma were included in some of these one-center studies, and more patients were treated with chemotherapy. It does appear, however, that the general use of radiotherapy for all deep-seated, high-grade soft tissue sarcomas yields better local control, but better control does not improve survival (Rööser et al 1990, Gustafson 1994, Lewis et al 1997, Trovik et al 2000a. Hence, the morbidity associated with radiotherapy may not be justified to attain a 10% reduction in the recurrence rate (Sugerbaker et al 1982, Bell et al 1989, Stinson et al 1992, Wiklund et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…The studies cannot be readily compared with ours since patients with recurrent sarcoma were included in some of these one-center studies, and more patients were treated with chemotherapy. It does appear, however, that the general use of radiotherapy for all deep-seated, high-grade soft tissue sarcomas yields better local control, but better control does not improve survival (Rööser et al 1990, Gustafson 1994, Lewis et al 1997, Trovik et al 2000a. Hence, the morbidity associated with radiotherapy may not be justified to attain a 10% reduction in the recurrence rate (Sugerbaker et al 1982, Bell et al 1989, Stinson et al 1992, Wiklund et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of local recurrence on the overall survival in soft tissue sarcomas of the extremities is not clear [10,16,25,31]. Two previous prospective studies have concluded local recurrences had no influence on survival.…”
Section: Introductionmentioning
confidence: 99%
“…3,9,10 Currently, it is recognized that, although such terms are useful in the planning of a surgical procedure, the crucial determinant of adequacy of resection is the actual microscopic resection margin. [11][12][13][14][15][16][17][18][19] In virtually all reports, positive resection margins are correlated with a significantly heightened risk for local recurrence [11][12][13][14][15][16][17] ; and, in some reports, positive resection margins also are correlated with an increased risk of developing metastatic disease and a poorer disease specific survival. 11,15,16 Thus, the achievement of negative resection margins is an important therapeutic principle for patients with STS.…”
mentioning
confidence: 99%